2020
DOI: 10.1108/jbim-10-2019-0463
|View full text |Cite
|
Sign up to set email alerts
|

Adapting sales influence tactics in the information intensive era

Abstract: Purpose This paper aims to explore the usage of selling influence tactics across prospective customers with differing information-related needs. Design/methodology/approach The research study uses an exploratory critical incident technique (CIT) methodology to identify and examine salesperson influence tactics. Findings This study identifies and explores the use of salesperson influence tactics across three information-based conditions often encountered by salespeople (i.e. information seeking customers, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Resource integration happens when institutions, as in this eHealth service ecosystem, coordinate the reconfiguration (Edvardsson et al , 2014). Data clearly show that partnerships at all levels can boost skills and activities in a certain period and in a context in which new collaborations continuously modify resource combinations (Leach et al , 2020; McFarland, 2019). The meso level is gaining a pivotal role in this process, representing the privileged locus of interaction among service providers, hospitals, health tech start-ups, patients’ associations and the like, because the process of change requires overcoming barriers and tensions and the creation of convergent logics not only among the different actors (Jaakkola et al , 2019) but also among the different levels.…”
Section: Discussionmentioning
confidence: 97%
“…Resource integration happens when institutions, as in this eHealth service ecosystem, coordinate the reconfiguration (Edvardsson et al , 2014). Data clearly show that partnerships at all levels can boost skills and activities in a certain period and in a context in which new collaborations continuously modify resource combinations (Leach et al , 2020; McFarland, 2019). The meso level is gaining a pivotal role in this process, representing the privileged locus of interaction among service providers, hospitals, health tech start-ups, patients’ associations and the like, because the process of change requires overcoming barriers and tensions and the creation of convergent logics not only among the different actors (Jaakkola et al , 2019) but also among the different levels.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding relational network dimension, an interesting finding was that they declined in adaptation and a soft intermediation process. We know that suppliers must be increasingly adaptable with respect to changing customers’ needs (Leach et al, 2020; McFarland, 2019); however, this is amplified in a digital setting. The velocity of interactions dramatically increased.…”
Section: Discussionmentioning
confidence: 99%
“…The granular processes we identified are indeed relevant because if they are not properly managed, they will limit or destroy value creation (Vafeas et al, 2016). For instance, misalignment could frequently occur in a digital context due to the diversity of interaction environments (Araujo and Kjellberg, 2015), and ambiguity could emerge when resource combinations are modified and new reference points are needed to assess the value created within the collaboration (Leach et al, 2020; McFarland, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, well‐informed consumers tend to rely heavily on their own inferences and avoid sales interactions (Hochstein et al, 2021; Wood & Lynch, 2002). Previous research has suggested adaptive selling strategies for retailers to handle well‐informed consumers (Hochstein et al, 2019, 2021; Leach et al, 2020; Li et al, 2014). However, little attention has been given to understanding why well‐informed consumers avoid personal contact with salespeople (Hochstein & Bolander, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested adaptive selling strategies for retailers to handle well-informed consumers (Hochstein et al, 2019(Hochstein et al, , 2021Leach et al, 2020;Li et al, 2014). However, little attention has been given to understanding why well-informed consumers avoid personal contact with salespeople (Hochstein & Bolander, 2018).…”
mentioning
confidence: 99%